2019
DOI: 10.3390/ma12162645
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Foundry Sand Concrete under Ambient and Elevated Temperatures

Abstract: Waste foundry sand (WFS) is the by-product of the foundry industry. Utilizing it in the construction industry will protect the environment and its natural resources, and enable sustainable construction. WFS was employed in this research as a fractional substitution of natural sand by 0%, 10%, 20%, 30%, and 40% in concrete. Several tests, including workability, compressive strength (CS), splitting tensile strength (STS), and flexural strength (FS), ultrasonic pulse velocity (USPV), Schmidt rebound hammer number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
(77 reference statements)
1
16
0
Order By: Relevance
“…The heat of hydration of GPC is higher than that of OPC concrete due to the vigorous geopolymerization process of aluminosilicates activated with alkaline activators [123,124]. Singh et al [125] investigated the effect of alkaline activator on strength properties of FA/slag geopolymer concrete.…”
Section: Heat Of Hydrationmentioning
confidence: 99%
“…The heat of hydration of GPC is higher than that of OPC concrete due to the vigorous geopolymerization process of aluminosilicates activated with alkaline activators [123,124]. Singh et al [125] investigated the effect of alkaline activator on strength properties of FA/slag geopolymer concrete.…”
Section: Heat Of Hydrationmentioning
confidence: 99%
“…Many researchers examined the influence of different nanomaterials on cement paste flow properties [ 123 , 124 , 125 , 126 , 127 , 128 ]. Ormbsy et al [ 123 ] used the parallel plate geometry for rheological investigation and found that MWCNTs meaningfully influenced the rheological behaviour of polymerizing cement.…”
Section: Rheological Properties Of Graphene Cement Pastementioning
confidence: 99%
“…The geopolymer sample exhibited a lower strength than the control sample, which was expected due to the reaction between silicon dioxide and cement paste under the high alkaline environment in the geopolymer concrete samples. This may be attributed to the composition of SCBA composition and its particle size distribution [49]. The presence of pores and voids caused a higher absorption, resulting in a lesser compressive strength.…”
Section: Permeable Porosity Testmentioning
confidence: 99%